Perception of language variation in the speech of Singaporean political leaders - Lim, Sheryl W. X.; Ng, Bee Chin (World Englishes, 2025)
Though politicians consciously or unconsciously vary their speech style to create a more positive response from the voting public, we have little empirical evidence attesting to its effectiveness. This study investigates the attitudes of 254 Singaporeans (aged 21–70) towards the use of two English varieties, Standard Singapore English (SSE) and Colloquial Singapore English (CSE) by politicians using both a modified matched‐guise technique followed up with a semi‐structured interview. Participants listened to enacted recordings of political speeches in both English varieties and made personality trait ratings. The results reveal that SSE is rated significantly higher on trustworthiness, reliability and status and these are correlated with higher socioeconomic status. Age‐related patterns are found for the solidarity traits as the younger adults evaluate CSE significantly more favourably. This paper presents a nuanced analysis of English as a political language medium and the ideologies that contribute to resistance or support for the different English varieties.